Leopard tortoise Stigmochelys pardalis (Bell, 1928) mortality caused by electrified fences in central South Africa and its impact on tortoise demography. Issue 1 (2nd January 2021) - Holt, Sharon; Horwitz, Liora Kolska; Wilson, Beryl; Codron, Daryl
ABSTRACT: The leopard tortoise ( Stigmochelys pardalis ) is among the most ubiquitously distributed chelonian species in Africa. As with other chelonians, however, the species' slow growth rate, coupled with low survivorship of juveniles, make it susceptible to declines under regimes of environmental perturbation. Here we studied the impact of electrified fences, a key source of mortality for many South African terrestrial vertebrate taxa, on leopard tortoise mortality in the Free State Province (Jacobsdal district) and Northern Cape Province (Strydenburg district), and its implications for survivorship of this population. Our results show a strong selection bias towards larger (breeding age) individuals that, given the life history of the species, should have strong (negative) consequences for populations. Using data for tortoise populations from other regions as a baseline for survivorship rates in populations unaffected by fencing, we derived a size-structure matrix model to evaluate the impact on population growth rates. Population projections, taking into account variation in survivorship and reproductive rates across and within size classes, indicated substantially higher risk of negative population growth (and eventual extinction) in populations affected by electrified fences. These results confirm that fencing is a conservation problem for the leopard tortoise population in this, and probably other regions, and highlights an urgent need for more intensive regulation of electrified fencing practices among landowners.